Barbaric, Damir (2015). Chora. Über das zweite Prinzip Platons. Attempto Verlag, Tübingen - Herkert, Felix (Revista Archai, 2017)
Herkert, Felix (2017). Rezension: Barbaric, Damir (2015). Chora. Über das zweite Prinzip Platons. Attempto Verlag, Tübingen.